نظرية الحفر والنفر في القرآن الكريم - السكر، فايزة إبراهيم محمد; الرواجفة، أيمن عيد (ديوان الوقف السني - مركز البحوث والدراسات الإسلامية, 2023)
عبر النظرة الفاحصة المتأنية والقراءة التدبرية للقرآن الكريم نلحظ أسلوبا لم تتعرض له الدراسات السابقة في ترتيب الجمل في الآية القرآنية الكريمة أو في ظهور الآية الكريمة في السورة بشكل مختلف عن آيات السورة من حيثيات عدة من قبيل مثل طول الآية نسبة لآيات السورة أو اختلاف الفاصلة القرآنية للآية الكريمة فجأة أو اختلاف ظاهر في التعبير عن موضوع السورة، ودراسة ظهور بعض الآيات وبعض السور في سياقات مختلفة عن السياقات التي ظهرت فيه وغير ذلك. وقد جاء هذا البحث ليتتبع هذه الآيات والسور وليطرح أمثلة عليها، لنثبت هذا النوع الجديد من مظاهر إعجاز القرآن الكريم هذا النظم الكريم والحكمة من خروج هذه السور والآيات الكريمة عما يتوقعه القارئ أو السامع. وهذا البحث يتناول مجموعة من الآيات الكريمة التي ظهرت مختلفة في صياغتها أو معناها أو فاصلتها عن آيات سورتها، وبعض السور التي ظهرت بشكل مختلف عن الجزء الذي وردت فيه أو السور التي قبلها أو السور التي بعدها، والآية الكريمة التي ترد فيها عبارة تركز معناها وتكون هي واسطة المعنى ولبه. Through a careful look and reflective reading of the Holy Qura’n, we noticed a form that was not known before in the order of the sentences in the Qur’anic verse, or in the form of the appearance of the verse in a different way from several circumstances, such as the length of the verse in proportion to the verses of the surah or the difference of the Qur’anic comma of the verse suddenly or an apparent difference in expressing a surah topic. There are verses and surahs that appeared different from the context in which they were mentioned. The purpose of this research is to present examples of them and to clarify the aspects of miraculousness and the wisdom of the departure of these surahs and noble verses from what the reader or listener expects. This research deals with a group of noble verses that appeared different in their formulation or meaning or their separation from the verses of its surah, and some of the surahs that appeared in a different way from the part in which they were mentioned or the surahs before them or the surahs after them, and the verse in which is a phrase that focuses in its meaning and is the intermediate meaning and its core.
Keywords: القرآن الكريم -- التفسيرات القرآنية -- العلوم الإسلامية -- الحفر والنفر